Learning from the success of tobacco control: how to leverage ideas, interests, and institutions to reduce red meat consumption - Bless, Anja (Frontiers in Sustainability, 2023)
Over-consumption of red meat has significant impacts on public health and the environment. To achieve a planetary health diet, consumption of red meat must be reduced across the developed world. However, policy action on this issue has been lacking and there is insufficient research exploring how to overcome barriers to reducing red meat consumption. Using the ‘three I’s’ policy change framework based around ideas, interests, and institutions and their influence on policy outcomes, this article will consider how the passage and success of Australia’s tobacco control regime could provide lessons for achieving reductions in Australian red meat consumption. Drawing on stakeholder analysis through semi-structured interviews, this analysis demonstrates the explanatory power of the ‘three I’s’ framework and highlights the essential roles of awareness-raising, cohesive policy networks, and a gradual increase in interventionism for achieving transformative changes in consumption behavior. It also demonstrates the scale of barriers for policies aimed at reducing red meat over-consumption, and the potential policy windows that are opening due to a shift in meat consumption patterns.